The Existence of Lasem Batik Entrepreneurs during the Covid-19 Pandemic - Nanang Adie Setyawan (Politeknik Negeri Semarang, 2021)
This research was conducted to determine the existence of batik lasem entrepreneurs in Rembang district during Covid-19 pandemic. Respondents were all batik lasem entrepreneurs according to data from The Department of Industry, Trade, Cooperatives and SMEs, Rembang Regency, totaling 120 entrepreneurs. This study uses confirmatory factor analysis techniques and maximum likelihood estimation in SEM (Structural Equations Modeling) from the statistical package AMOS 24.0 (Analysis of Moment Structure). The data collection technique used a questionnaire with a semantic differential scale. The results of study is consistent with the hypothesis which shows that entrepreneurial orientation significantly affects the performance of the batik SME business with a koefisien standardized estimated 0.451 and P-value ***, as well as environmental adaptability has a positive effect on the batik SME business performance with a koefisien standardized estimated 0.555 and P-value ***. From this research it can be learned that entrepreneurs can still rise from adversity during covid 19 pandemic if they are able to adapt to the current environment that tends towards digitalization while still hold firmly to the principles of entrepreneurship